A hierarchical extension of a multiple-component scattering model with unitary transformation of the coherency matrix. Issue 11 (2nd November 2019) - Wang, Yu; Yu, Weidong; Wang, Chunle
ABSTRACT: The overestimation of volume scattering (OVS) is an essential shortcoming of the model-based polarimetric synthetic aperture radar (PolSAR) target decomposition method. It is likely to affect the measurement accuracy and result in mixed ambiguity of the scattering mechanism. In this paper, a hierarchical extended multi-component decomposition method (ExMCSM) that can adaptively select the refined volume scattering models based on the artificial area extraction result is proposed for overcoming the OVS. First, artificial areas are extracted from the image to distinguish between artificial areas and non-artificial areas. Then, orientation angle compensation (OAC) and helix angle compensation (HAC) are applied to the coherency matrix to reduce the complexity of the operation. Finally, the volume scattering model of each pixel is refined to more effectively adapt to various scattering mechanisms. Spaceborne Gaofen-3 full PolSAR data are used to evaluate the performance of the proposed decomposition method. The experimental results demonstrate that the proposed decomposition method can accurately represent the scattering characteristics of the ambiguous regions and the oriented building areas can be well discriminated as dihedral or odd-bounce structures.